Pengaruh Kualitas Pelayanan dan Beban Kerja Dokter Gigi terhadap Kecemasan Pasien di Klinik Gigi I-Dental Care Jakarta Selama Masa Pandemi Covid-19 Tahun 2022-2023 - Rahmi Dinawati; Budiharto; Zahera Mega Utama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to explain the influence of service quality and workload on patient anxiety at the I-Dental Care dental clinic in South Jakarta during the Covid-19 pandemic. The method used in this research is a descriptive method. The approach used is a quantitative approach. In this study, the author took samples using the saturated sample method or research census, namely taking all patients who visited the I-Dental Care clinic for one month. The research subjects in this study were 105 patients and dentists at the I-Dental Care Clinic. The data analysis techniques used are validity tests, reliability tests, descriptive analysis and inferential statistical data analysis. Research results show that service quality influences patient anxiety at the I-Dental Care Clinic during the Covid-19 pandemic. Workload influences patient anxiety at the I-Dental Care Clinic. Service Quality and Workload Influence Patient Anxiety at the I-Dental Care Clinic during the Covid-19 pandemic.